Effective and selective adsorption of phosphate from aqueous solution via trivalent-metals-based amino-MIL-101 MOFs - Liu, Ruiting; Chi, Lina; Wang, Xinze; Wang, Yuan; Sui, Yanming; Xie, Tingting; Arandiyan, Hamidreza (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •Amino-MIL-101(Al/Fe) MOFs was applied in high strength phosphate adsorption.•Fast kinetics, high sorption capacity and strong selectivity were demonstrated.•Electrostatic attraction and ligand exchange were identified as the main mechanisms. Although adsorbents for phosphate removal from eutrophic water have been widely explored, it remains a critical challenge to develop robust and highly selective phosphate adsorbents featuring abundant binding sites and high affinity. In this work, two stable metal-organic frameworks (MOFs) of amine functionalized MIL-101 based on trivalent metal aluminum and iron were synthesized by simple solvothermal methods and applied as adsorbents to capture phosphate ions of high strength. Phosphate adsorption kinetics, isotherm behavior, and solution matrix effects (eg. solution pH, coexisting ions and ionic strength) were reported. Results showed that trivalent metal based NH2-MIL-101 MOFs outperformed most adsorbents ever reported, exhibiting fast kinetics and high maximal adsorption capacity above 79.414 mg P/g at 298 K, pH independence in the range from 3 to 11, less sensitivity to ion strength, strong selectivity for phosphate in presence of competing ions and could be easily regenerated and re-applied for phosphate removal. It was noticeable that phosphate adsorption performance varied on the two kinds of trivalent metals based MOFs due to their difference in morphology, surface and interface properties including zeta potential, chemical affinity toward target anion and the types of complexation formed with phosphate. NH2-MIL-101(Al) showed faster kinetics, while NH2-MIL-101(Fe) has higher affinity toward phosphate. Furthermore, based on Fourier transform infrared (FTIR), X-ray photoelectron spectroscopy (XPS) spectra and zeta potential analysis, electrostatic attraction and ligand exchange were identified as the main phosphate adsorption mechanisms by NH2-MIL-101(Al/Fe). Besides, the functionalized adsorbents with amine group further enhanced the phosphate removal capacities by providing extra surficial positive charges. These findings demonstrate that trivalent metal based NH2-MIL-101 is a promising candidate for phosphate adsorption from aqueous solution with high efficiency and selectivity.